Recycling of waste cathode ray tube glass through fly ash-slag geopolymer mortar. (7th March 2022) - Long, Wu-Jian; Zhang, Xuanhan; Xie, Jing; Kou, Shicong; Luo, Qiling; Wei, Jingjie; Lin, Can; Feng, Gan-Lin
Highlights: Recycling of hazardous cathode-ray tube (CRT) glass by fly ash-slag geopolymer mortar was studied. Effect of alkali dosage and silica modulus on mechanical and Pb solidification performance was elaborated. Higher alkali dosage results in weak interfacial transition zone (ITZ) and lower total porosity. Increasing silica modulus improves physical encapsulation and chemical solidification of Pb. The optimal alkali dosage and silica modulus are 6% and 1.5 for fly ash-slag geopolymer mortar containing CRT glass aggregate. Abstract: Large amount of waste cathode ray tube (CRT) glass containing the hazardous heavy metal Pb, discarded at landfill sites without proper recycling method, poses a great threat to the environment and public health. It is urgent to develop an effective and efficient recycling method to minimize the quantity of these hazardous wastes. In the present study, recycling of waste CRT glass as fine aggregate through fly ash-slag geopolymer composite were studied. The compressive strength, alkali-silica reaction expansion (ASR expansion) and Pb leaching of fly ash-slag geopolymer mortars containing CRT glass (FSGM-CRT), considering influence of silica modulus and alkali dosage, were comprehensively studied through toxicity characteristic leaching procedure (TCLP) test, X-ray diffraction (XRD), thermogravimetry (TG), Fourier transform infrared (FTIR) spectroscopy and scanning electron microscope (SEM). The results showed that the solidification mechanism of geopolymer for waste CRT glass includes not only physical encapsulation, but also chemical solidification. As the silica modulus increased, the compressive strength and the ASR expansion first increased and then decreased, and the leached concentration of Pb significantly decreased. The increased silica modulus improves the chemical binding of Pb ions by generating lead silicate as it is resulted by microstructure evolution tests. Additionally, increase of silica modulus can significantly improve the interfacial transition zone (ITZ) and the total porosity, resulting in better physical encapsulation performance on the leached Pb ions. On the contrary, higher alkali dosage can hinder the polycondensation reaction of silicate and aluminum tetrahedrons, inhibiting the polymerisation of the geopolymer mortars, thus leading to weakening of both the solidification performance and the compressive strength of FSGM-CRT. Considering combined structural and solidification performance requirements on compressive strength, ASR expansion and Pb leaching limit, the optimal alkali dosage and silica modulus for recycling CRT with geopolymer is 6% and 1.5, respectively.